Learning about learning styles: Pedagogical, curricular, and managerial implications - Segumpun, Reynaldo G.; Adam, Mohamad Zainol Abidin (2004)
The way students acquire knowledge is an interesting issue and an important research agendum. Better understanding of the learning styles and their characteristics is a necessity not only to educators but also to learners (Vincent and Ross, 2001) because of the benefits if offers to both parties. This paper looked into the learning styles of secondary school students in a science boarding school in the state of Kedah, Malaysia. Specifically, it sought to determine what are the learning styles of science-stream students as well as identify if are there significant differences in the students’ learning styles grouped by gender, position in class, sibling order, father’s occupation, mother’s occupation, educational attainment of father, and educational attainment of mother.A Personal Learning Style Inventory (Wyman, 1999) was utilized in determining the learning styles of Forms 1, 2, 3, 4, and 5 students. Data were analyzed via SPSS at .05 alpha. Findings showed that generally, the respondents’ learning styles was auditory. Learning styles differed significantly by gender and sibling order. Implications on curriculum, teaching, and educational management are discussed.